Assessing the Use of Long Lasting Insecticide Treated Nets among Pregnant Women in Ga East Municipality of the Greater Accra Region - Twumasi, C. (University of Ghana, 2015)
Background: Malaria is a disease which is caused by the plasmodium parasites in the blood or tissues of humans. In 2012, government of Ghana distributed bednets to pregnant women in order to reduce the transmission of malaria. Though there was a massive distribution all over the country, the consistent use of the LLIN is low. Thus this study was done to find out the use of LLIN among pregnant women in the Ga- East Municipality and find out the factors that influence the use of the bednets in the municipality. Methods: The study used a cross-sectional quantitative method. The data was collected using structured questionnaires. A simple random sampling method was used in the selection of 206 participants for the study. SPSS and Microsoft Excel were used to analyze the data. Results: The pregnant women 97.1% (200) in the Municipality had knowledge about transmission of malaria. More than half of them 53.9% (111) had very good knowledge about LLIN use and that was significant. Some of the participants 61.7% (127) had misconceptions about the use of LLIN. Despite their high level of knowledge about malaria transmission and use of LLIN, the level of usage of LLIN among the pregnant in the two sub-municipalities (Abokobi and Haatso) in the Ga East Municipality was low 43.2%. Usage of LLIN here means that, the pregnant women who slept under the LLIN the night before the day of data collection for the study. The use of LLIN was related to educational level, occupation and marital status though not statistically significant
Thesis (MPh) - University of Ghana, 2015
Keywords: Insecticide Treated Nets; Pregnant Women; Malaria; Plasmodium Parasites